Transforming The Role of Religious Office Affairs to Reduce the Divorce Rate in Padang City - Syaiful Syaiful (JEICI - Journal of Education and Islamic Contemporary Issue, 2026)
This study aims to analyze the strengthening of the role of the Office of Religious Affairs (KUA) in reducing the rate of household divorce in Padang City through the Pusaka Sakinah program, the strategies of religious counselors, and the strengthening of socio-religious family service regulations. This research employed a qualitative, descriptive-analytical approach. Data were collected through observation, in-depth interviews, and documentation at several KUA offices in Padang City, particularly in Kuranji, North Padang, and West Padang Districts. The findings reveal that KUA no longer functions solely as an administrative institution for marriage registration but has been transformed into a socio-humanistic institution that plays an important role in strengthening family resilience. The Pusaka Sakinah program is implemented through premarital guidance, family counseling, household conflict mediation, family development programs, and continuous religious counseling. Religious counselors serve as mediators, counselors, and facilitators in resolving family conflicts. The study also found that the program's success was influenced by local government support, cross-sector collaboration, and the integration of Minangkabau cultural values into family counseling activities. Nevertheless, several challenges remain, including limited human resources, low public participation, social stigma toward counseling services, and challenges related to the digitalization of KUA services. This study concludes that strengthening regulations, standardizing services, improving the competence of religious counselors, and implementing preventive approaches grounded in local cultural values are important strategies for reducing divorce rates and strengthening Muslim family resilience in Padang City.